Pelaksanaan Pemungutan, Penyetoran, Dan Pelaporan Pajak Pertambahan Nilai Atas Usaha Jasa Konstruksi Oleh PT. Arkonin - Aprilia Dewi; Nita Mustika (CV. Astina Mandiri, 2022)
Construction services are one of the services that are quite developed in this country. The stipulation of Law Number 18 of 1999 concerning Construction Services is used as the basis for the development of national construction services. The construction service business is also a unique type of business because it is incidental (only runs from time to time when getting a project/contract). This causes tax revenues for construction services, especially Value Added Tax, to be uncertain every year (because tax revenues can go up or down). The research was conducted at PT. Arkonin is engaged in construction services. The purpose of writing this thesis is to determine the implementation of the collection, deposit, and reporting of Value Added Tax at PT. Arkonin is in accordance with the provisions of the applicable tax regulations. The author conducted this research with an analytical descriptive method. Namely observations (observations) on the object of research, interviews with resource persons related to research problems, and library research. From the results of the study, the authors conclude that the implementation of the collection, deposit and reporting of Value Added Tax is carried out by PT. Arkonin outside the correction is actually in accordance with the applicable PPN and PPnBM Law. Constraints faced by PT. Arkonin in fulfilling Value Added Tax obligations, namely when transacting with Collectors (Government Treasurer) and the Collector is often late in providing proof of collection.